INTERDISCIPLINARY CONTEXT OF MASTERS – THE FUTURE TEACHER-PHILOLOGIST PEDAGOGICAL TRAINING UNDER THE RAPID DEVELOPMENT OF INFORMATION AND COMMUNICATION TECHNOLOGIES - Koval, Tamara (Continuing Professional Education: Theory and Practice, 2019)
The article deals with the analysis of the scientific and methodological works on the complex characteristics of the category of interdisciplinarity. The features of the educational process of Masters – future teachers philologists in the context of interdisciplinary, technological competence and approaches are investigated. Theoretical aspects of the concept of «ICT competence of a teacher-philologist» as an integrative quality of the individual that determine its preparedness and ability to use in educational activities of information and communication technologies to satisfy their individual needs and the formation of general and professional (language and speech) competencies in learning foreign languages are the problems of our research. Organizational and pedagogical conditions of interdisciplinary research of multimedia electronic educational resources in the masters teacher training, such as the formation of a certain level of general and professional (subject) competencies, including the development of ICT competence and interdisciplinary vision of their future professional activity in the direction of technologizing; implementation of the content of teacher training masters content modules as «Еducational use of ICT technologies in teaching foreign languages», «Actual problems of pedagogy high school in the conditions of informatization of education», «Еlectronic multimedia educational resources as objects of interdisciplinary research» and so on; the use of methods of study on the feasibility of creating and using multimedia electronic educational resources in the educational activity – electronic teaching systems, multimedia electronic textbooks, case studies, teaching materials in distance learning systems such as, eg, Moodle and others are the main subjects of the article. The necessity of teacher training in the Masters interdisciplinary research multimedia electronic educational resources teaching foreign languages in terms of professional, methodical, psychological, didactic, technology and software and statistical ones is underlined by the author.